Natural Convection Cooling of an Array of Flush Mounted Discrete Heaters Inside a 3D Cavity (Advances in Applied Mathematics and Mechanics, 2018)
An investigation of natural convective flow and heat transfer inside a threedimensional rectangular cavity containing an array of discrete heat sources is carriedout. The array consists of a row and columnwise regular arrangement of identicalsquare shaped isoflux discrete heaters and is flush mounted on a vertical wall of thecavity. A symmetrical isothermal sink condition is maintained by cooling the cavityuniformly from either the opposite wall or the side walls or the top and bottom walls.The other walls of the cavity are maintained adiabatic. A finite volume method basedon the SIMPLE algorithm and the power law scheme is used to solve the conservationequations. The parametric study covers the influence of pertinent parameters such asthe Rayleigh number, the Prandtl number, side aspect ratio of the cavity and cavityheater ratio. A detailed fluid flow and heat transfer characteristics for the three casesare reported in terms of isothermal and velocity vector plots and Nusselt numbers.In general, it is found that the overall heat transfer rate within the cavity for $Ra =10^7$ is maximum when the side aspect ratio of the cavity lies between 1.5 and 2. A morecomplex and peculiar flow pattern is observed in the presence of top and bottom coldwalls which in turn introduces hot spots on the adiabatic walls. Their location and sizeare highly sensitive to the side aspect ratio of the cavity and hence offers more effectiveways for passive heat removal.